Comparative spatial inequality dynamics: The case of Mexico and the United States. (July 2015) - Rey, Sergio J.; Sastré Gutiérrez, Myrna L.
Abstract: In this paper we examine the trajectory of regional income inequality dynamics for two neighboring national systems. Using data on 3038 US counties and 2418 Mexico municipios, from 2000, 2005, and 2010, we employ recent extensions of spatial Markov chains and space-time mobility measures, to consider the following questions: Are regional inequality dynamics fundamentally distinct between Mexico and the United States? Does the role of spatial context influence the distributional dynamics of the two systems? Finally we examine if there is a distinct international border region that displays inequality dynamics different from those of the internal regions of the two national systems. Strong evidence of spatial heterogeneity in regional income mobility is found between the two national systems, with Mexico having higher mobility relative to the US. The international border region is found to have distinct mobility dynamics from either national system, experiencing the strongest mobility. Extensive evidence of spatial contextual effects are found throughout the US-Mexican pooled data set indicating that a region's transitional dynamics are influenced by incomes of neighboring regions. Highlights: A bi-national comparative perspective on income inequality dynamics in US and Mexico. Greater spatial income mobility with higher income dispersion for Mexico, relative to the US. A sort of first and second geographic feature characterizes this bi-national system. In both countries income transitional dynamics are conditional upon spatial context. Spatial income mobility in the international border region is found to be greater than in either national system.